Analisis Kebijakan Rehabilitasi Bagi Penyalahguna Narkotika di Indonesia - Anisya Ramdlonaning; Eva Achjani Zulfa (Universitas Semarang, 2023)
This study aims to analyze the problem of narcotics rehabilitation policies in Indonesia. The number of abusers who should get rehabilitation but imprisoned causes social reintegration of abusers not to be achieved. Because in prison the negative effects are greater than the effects of narcotics itself. In addition, the imprisonment causes the prison and detention capacity that occurs in almost all regions of Indonesia. Research uses the method of formulation of multiple perspective analysis that sees from three aspects of the problem, namely from the personal aspect (narcotics abusers), organizational aspects (institutions that carry out rehabilitation) and technical aspects (law enforcement officials). The source of the data studies and semi -structured literature studies. The results that the basis of resistant abusers' problems for treatment, there is no national standard for rehabilitation services from input s.d output/outcome, it is difficult for narcotics abusers to meet the requirements to be rehabilitated cumulative Not proven in the network, the lack of clear subjects of narcotics abusers regulated in regulations that regulate so that there are differences in APH interpretation. The novelty in this study uses different research methods that aim to see problems from three different points of view. So that a source of rehabilitation policy problems can be found for narcotics abusers. Penelitian ini bertujuan untuk menganalisis permasalahan kebijakan rehabilitasi narkotika di Indonesia. Banyaknya penyalahguna yang seharusnya mendapatkan rehabilitasi akan tetapi dipenjara menyebabkan reintegrasi sosial penyalahguna tidak tercapai. Karena didalam penjara efek negatifnya lebih besar daripada efek narkotika itu sendiri. Selain itu pemenjaraan tersebut menyebabkan over kapasitas Lapas dan Rutan yang terjadi hampir diseluruh wilayah Indonesia. Penelitian menggunakan metode perumusan masalah analisis perspektif berganda yang melihat dari tiga aspek permasalahan yaitu dari aspek personal (penyalahguna narkotika), aspek organisasional (lembaga yang melaksanakan rehabilitasi) dan aspek teknis (aparat penegak hukum). Sumber datanya studi kepustakaan dan wawancara semi terstruktur. Hasil penelitian bahwa dasar permasalahan Penyalahguna resisten untuk berobat, belum ada standar nasional layanan rehabilitasi dari input s.d output/outcome, Sulit bagi penyalahguna narkotika memenuhi persyaratan untuk dapat direhabilitasi secara kumulatif yaitu tertangkap tangan, urin positif, barang bukti dibawah gramatur, ada hasil asesmen dan tidak terbukti dalam jaringan, Kurang jelasnya subyek penyalahguna narkotika yang diatur dalam peraturan yang mengatur sehingga terjadi perbedaan penafsiran APH. Kebaruan dalam penelitian ini menggunakan metode penelitian yang berbeda yang bertujuan untuk melihat permasalahan dari tiga sudut pandang yang berbeda. Sehingga dapat ditemukan sumber permasalahan kebijakan rehabilitasi bagi penyalahguna narkotika.